2023
DOI: 10.1097/md.0000000000034059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for severe linezolid-associated thrombocytopenia in pediatric patients: An analysis of a public database

Abstract: Linezolid is widely used in various clinical settings. Studies have revealed that it may cause thrombocytopenia in adults. However, the correlation between the use of linezolid and thrombocytopenia in pediatric patients is still unclear. This study aimed to identify the impact of Linezolid on the occurrence of thrombocytopenia in children. A retrospective observational study was conducted using data on patients treated with linezolid from the Pediatric Intensive Care clinical database. Univariate and multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…A similar nding was reported for low baseline platelet count by Duan et al in neonates [47] and by Choi et al in adults [51], and by Thi Phuong et al for sepsis/septic shock in adults [52]. Other studies demonstrated that the concomitant use of meropenem, piperacillin/tazobactam, levo oxacin, or caspofungin was a risk factor for the development of thrombocytopenia in patients receiving linezolid [53][54][55]. It was an anticipated nding that the number of patients receiving meropenem and linezolid combination therapy in ICU patients would be higher than other combination therapies considering the antimicrobial resistance pro le of the ICUs.…”
Section: Discussionsupporting
confidence: 78%
“…A similar nding was reported for low baseline platelet count by Duan et al in neonates [47] and by Choi et al in adults [51], and by Thi Phuong et al for sepsis/septic shock in adults [52]. Other studies demonstrated that the concomitant use of meropenem, piperacillin/tazobactam, levo oxacin, or caspofungin was a risk factor for the development of thrombocytopenia in patients receiving linezolid [53][54][55]. It was an anticipated nding that the number of patients receiving meropenem and linezolid combination therapy in ICU patients would be higher than other combination therapies considering the antimicrobial resistance pro le of the ICUs.…”
Section: Discussionsupporting
confidence: 78%